MOISTURIZING EFFECTIVENESS OF ORGANIC LIP CREAM FORMULATION WITH BEETROOT EXTRACT (Beta vulgaris L) AND CHIA SEED OIL (Salvia hispanica) - Dela Amalia Putri; Chaidir Chaidir; Muhammad Hanafi (LPSDI Bina Patria, 2022)
The purpose of this study was to evaluate the quality parameters, safety and analyze the moisturizing effectiveness activity of Organic Lip Cream with beetroots extract (Beta vulgaris L) and Chia Seed Oil (Salvia hispanica). Methods: The beetroot extraction was optimized using 3 solvents and 2 types of cultivation (Conventional and Organic) and was determined its total Betalain assay (Betaine and Vulgaxhantin) was. The quality parameter of lip cream was evaluated as physical appearance, texture, viscosity, adhesion test, pH, homogeneity, hedonic test, acute dermal irritation test, and stability. Testing the moisturizing effectiveness by measuring lip moisture content immediately after use, 4 hours after use, and after 3 days of routine use. Results: Organic beetroots contain a total of Betalain pigment concentration significantly higher than beetroots from conventional cultivation. The highest total betalain assay in the extract was performed by 96% ethanol solvent with the addition of 1-2 % citric acid (pH 5) compared to 70% ethanol solvent and water solvent. Organic lip cream with beetroots extract and chia seed oil is significantly effective to increase lip moisture immediately after use, 4 hours after use and after 3 days of routine use compare to baseline (before use). Organic lip cream with beetroot extract and chia seed oil was formulated with result meet specifications of good lip cream, are not irritative, has effectively increased lip moisture, acceptable by hedonic test (appearance of the preparation, sensation on the lips, adhesion and smearing power) and stable for 4 weeks at 40°C. Conclusion: Organic lip cream with beetroots extract and chia seed oil are meets specifications of quality control, safety, and efficacy (moisturizing effectiveness).